2014
DOI: 10.1177/0310057x1404200116
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Anaphylaxis to Sugammadex and a Protocol for Intradermal Skin Testing

Abstract: Sugammadex is a selective binding agent for aminosteroid neuromuscular blockers whose use is increasing in anaesthetic practice. We present three cases of severe anaphylaxis coincident with sugammadex administration. Subsequent intradermal testing confirmed sugammadex as the triggering agent, with all patients having positive skin responses to a 1:100 dilution of the standard 100 mg/ml solution and two out of three having a positive response to a 1:1000 dilution. As all patients were administered sugammadex to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 4 publications
(6 reference statements)
0
45
0
1
Order By: Relevance
“…Cases of anaphylaxis to sugammadex have been recently reported (63–65) being an IgE-mediated mechanism suggested in several cases as patients gave positive skin tests and flow cytometry results (66, 67). It has been suggested that treatment of rocuronium-induced anaphylaxis should include the administration of sugammadex (68, 69).…”
Section: Drugs Causing Anaphylaxismentioning
confidence: 99%
“…Cases of anaphylaxis to sugammadex have been recently reported (63–65) being an IgE-mediated mechanism suggested in several cases as patients gave positive skin tests and flow cytometry results (66, 67). It has been suggested that treatment of rocuronium-induced anaphylaxis should include the administration of sugammadex (68, 69).…”
Section: Drugs Causing Anaphylaxismentioning
confidence: 99%
“…Most frequently reported side effects of SUG administration are pain, nausea, coughing, headache or vomiting 2,10, being the hypersensitivity reactions, ranging from erythema to anaphylactic shock, are the most alarming among them 27,28,29. Furthermore, allergy to NMB has been considered the first cause of perioperative anaphylaxis 30,31.…”
Section: Discussionmentioning
confidence: 99%
“…ROC also has the potential to interact with other drugs, including aminoglycosides 34. The incidence of VEC-induced anaphylactic reactions is lower than those induced by ROC 28. Although SUG itself could induce hypersensitivity reactions, it was used to stop anaphylaxis induction by ROC, based on SUG design to encapsulate ROC 35.…”
Section: Discussionmentioning
confidence: 99%
“…Some reports described sugammadex‐induced anaphylactic reactions in adults . A previous study reported that incidence proportion of sugammadex‐induced anaphylactic reactions was estimated to be 0.003% .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Some reports described sugammadex-induced anaphylactic reactions in adults. [4][5][6][7][8][9][10] A previous study reported that incidence Accepted: 24 April 2018 DOI: 10.1111/pan.13401 proportion of sugammadex-induced anaphylactic reactions was estimated to be 0.003%. 7 However, the data were obtained from anesthesiologists on a voluntary basis, and may have been underreported.…”
Section: Introductionmentioning
confidence: 99%